2014
DOI: 10.1186/2251-6581-13-53
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and its correlated factors among children and adolescents of Ahvaz aged 10 – 19

Abstract: BackgroundPopulation-based studies for prevalence of metabolic syndrome (M.S) in children and adolescents are relatively rare. The aim of this study was to assess the Prevalence of M.S and correlated factors among children and adolescents aged 10 to 19 years in Ahvaz.MethodsIn this descriptive-analytical population- based study, 2246 children and adolescents, 10–19 years old (1113 male and 1133 female) in Ahvaz, were evaluated. Anthropometry, biochemical measurement and blood pressure (BP) were assessed. Modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
7
11
1
Order By: Relevance
“…Although in the study conducted by Rashidi et al, (2014) the variables such as age, sex and BMI were reported as factors affecting the risk of MS, but the prevalence of the MS was lower in women than men [29]. Considering what was above mentioned and according to the difference between the results of some studies conducted about the risk factors for MS, and increasing prevalence of noncommunicable diseases in recent years, as well as considering the fact that current estimates of the prevalence of MS in Iran-in the form of non-communicable diseases surveillance systemhave been conducted with a sample size that is suitable for the whole country and does not identify related risk factors, this study aimed at better understanding the prevalence of MS and its related risk factors in the middle-age population.…”
Section: Page 4 Of 15mentioning
confidence: 84%
See 1 more Smart Citation
“…Although in the study conducted by Rashidi et al, (2014) the variables such as age, sex and BMI were reported as factors affecting the risk of MS, but the prevalence of the MS was lower in women than men [29]. Considering what was above mentioned and according to the difference between the results of some studies conducted about the risk factors for MS, and increasing prevalence of noncommunicable diseases in recent years, as well as considering the fact that current estimates of the prevalence of MS in Iran-in the form of non-communicable diseases surveillance systemhave been conducted with a sample size that is suitable for the whole country and does not identify related risk factors, this study aimed at better understanding the prevalence of MS and its related risk factors in the middle-age population.…”
Section: Page 4 Of 15mentioning
confidence: 84%
“…In some studies, the prevalence of this syndrome has been reported in women higher than in men [2,28,19,21,12], which is consistent with the results of the present study. However, in some studies, the prevalence of MS was higher in men than in women [24,25,29].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these studies, Pitangueira et al [31] noted low levels of HDL-c in 58.2% of students from Recôncavo Baiano. Iranian children and adolescents aged 10 to 19 years showed an HDL-c prevalence of 24.1%, according to the modified NCEP/ATPIII criteria, and there were no differences between boys and girls [33]. Low concentrations of HDL-c may also be related to high physical inactivity [34], a lifestyle factor identified in our study (33%).…”
Section: Discussionmentioning
confidence: 62%
“…This is consistent with the findings of other studies that reported prevalence rates of metabolic syndrome ranging from 26.9 to 38.6% among obese children and adolescents, despite varied diagnostic criteria. 20,21 Compared to other criteria which employed percentile values, the IDF diagnostic criteria for metabolic syndrome set higher cutoff values. A comparison of 3 diagnostic criteria for metabolic syndrome done by Sangun et al reported similar proportions of metabolic syndrome (31 to 39%) among obese children and adolescents.…”
Section: Discussionmentioning
confidence: 99%